Ideological Transformations of the Socialist party of Serbia - Anastasia V. Maleshevich (Научно-аналитический вестник Института Европы РАН, 2024)
This study examines the ideological transformation of the Socialist Party of Serbia (SPS), successor to the League of Communists of Serbia, during Serbia’s transition to capitalism. A distinctive feature of the Serbian case is that reformed communists retained power until the arrival of the right-liberal opposition in 2000. The ideological analysis is based on two closely related concepts: democratic socialism and social democracy. The study demonstrates the reasons behind the SPS's choice in favor of democratic socialism and examines how the party shifted rightward compared to its original ideological stance. The factor of European integration played a significant role in the alignment of the SPS with the neoliberal consensus, generally shaping the behavior and ideological positions of domestic actors in potential candidate countries. The article analyzes the SPS programs from 1990, 1992, and 2010. According to the latest program, the SPS now occupies the position of a typical center-left European party.